68Ga-FAPI PET/CT Versus 18F-FDG PET/CT for Detecting Metastatic Lesions in a Case of Radioiodine-Refractory Differentiated Thyroid Cancer. (November 2021) - Fu, Hao; Fu, Jie; Huang, Jingxiong; Pang, Yizhen; Chen, Haojun
Abstract : Abstract: 18 F-FDG PET/CT is a useful imaging modality for detecting disease recurrence and metastases in patients with radioiodine-refractory differentiated thyroid cancer (RAIR-DTC). However, the sensitivity of 18 F-FDG PET/CT in RAIR-DTC is not very satisfactory. 68 Ga-FAPI is a promising PET tracer that allowed imaging of various types of cancer. In this case, 68 Ga-FAPI showed a far better signal-to-background ratio than 18 F-FDG for detecting the RAIR-DTC metastatic lesions, especially for detecting the small pulmonary metastases. Therefore, 68 Ga-FAPI may be a promising alternative to 18 F-FDG for detecting tumor recurrence and metastases in RAIR-DTC. It could also be used for guiding FAP-targeted radionuclide therapy.